Sustaining the Entrepreneurship in Rural Tourism Development - Sharif, Norhafiza Md (International journal of multicultural and multireligious understanding, 2018)
Entrepreneurs play an important role in sustaining rural tourism and formulation of sustainable strategies being the initiators of the tourism business and the engine of the local development. Therefore, it is necessary to stimulate the development of entrepreneurial activities for the recovery of rural tourism potential and regional traditions, maintaining local employment growth and increase living standards in line with identifies needs and priorities of regional human resources development. This article aims to discuss the involvement of local communities in development of rural tourism entrepreneurship as well as addressing the issue of entrepreneurship in rural tourism.